Phagocytic glioblastoma-associated microglia and macrophages populate invading pseudopalisades. Issue 1 (4th December 2019) - Saavedra-López, Elena; Roig-Martínez, Meritxell; Cribaro, George P; Casanova, Paola V; Gallego, José M; Pérez-Vallés, Ana; Barcia, Carlos
Abstract: Hypoxic pseudopalisades are a pathological hallmark of human glioblastoma, which is linked to tumour malignancy and aggressiveness. Yet, their function and role in the tumour development have scarcely been explored. It is thought that pseudopalisades are formed by malignant cells escaping from the hypoxic environment, although evidence of the immune component of pseudopalisades has been elusive. In the present work, we analyse the immunological constituent of hypoxic pseudopalisades using high-resolution three-dimensional confocal imaging in tissue blocks from excised tumours of glioblastoma patients and mimic the hypoxic gradient in microfluidic platforms in vitro to understand the cellular motility. We visualize that glioblastoma-associated microglia and macrophages abundantly populate pseudopalisades, displaying an elongated kinetic morphology across the pseudopalisades, and are oriented towards the necrotic focus. In vitro experiments demonstrate that under hypoxic gradient, microglia show a particular motile behaviour characterized by the increase of cellular persistence in contrast with glioma cells. Importantly, we show that glioblastoma-associated microglia and macrophages utilize fibres of glioma cells as a haptotactic cue to navigate along the anisotropic structure of the pseudopalisades and display a high phagocytic activity at the necrotic border of the pseudopalisades. In this study, we demonstrate that glioblastoma-associated microglia and macrophages are the main immune cells of pseudopalisades in glioblastoma, travelling to necrotic areas to clear the resulting components of the prothrombotic milieu, suggesting that the scavenging features of glioblastoma-associated microglia and macrophages at the pseudopalisades serve as an essential counterpart for glioma cell invasion. Abstract : In this article, Saavedra-Lopez and colleagues described that glioblastoma-associated microglia and macrophages infiltrate hypoxic pseudopalisades, a well-known invading niche of extremely aggressive brain tumours. They show these highly motile immune cells with great phagocytic capacity as a counterpart of the glioma cell invasion. Graphical Abstract: